SISTEM INFORMASI GEOGRAFIS PEMETAAN DAERAH RAWAN LONGSOR KOTA SAMARINDA BERBASIS WEB MENGGUNAKAN METODE SKOR DAN PEMBOBOTAN - Sry Wahyuni; Syafei Karim; Dawamul Arifin (Universitas Islam Balitar, 2021)
Landslide disaster occupies the second position of disasters that often occur in Samarinda City after the flood disaster and from this study the results of the level of vulnerability to landslides can be obtained. From the calculation results obtained 91.29% this application provides several aspects that can add information about landslide-prone areas and can provide useful information for recipients in the form of additional information related to landslides in Samarinda City. Samarinda City has an area of ​​718.00 km2 which has 10 sub-districts spread over several points in Samarinda City. There are four mappings used in this study, namely slope, soil type, rainfall and land use. Analysis of the data using the method of scoring and weighting where each of these parameters has a score and weight then performs an overlay technique to produce a map of landslide-prone areas. The application used is ArcMap in analyzing, calculating, making maps, evaluating units of each map that are influential (important) in landslide events.